The Application of Asa Berger Humour Technique by Sabri Yunus from The Dramaturgy Perception in â€œKaroot Komediâ€ (Harmonia: Journal of Arts Research and Education, 2018)
This paper aims to introduce Sabri Yunus as a Dramaturgy in Comedy especially in the popularised television program called â€œKaroot Komediâ€. The method used in conducting this research is qualitative descriptive through a survey. The data was obtained through observation, interview and also documentation studies. The object of the observation is the drama performance â€œKaroot Komediâ€ by Sabri Yunus. The researcher is the instrument for this research, who is also in charge in collecting the data, conducting the observation and interpret the research questions based on the object. The analysis was able to be conducted successful using the model Gotthold Ephraim Lessing, Miles and Huberman. The validity of the data obtained is examined by using the triangular method and also by the co-workerâ€™s evaluation and insight. The finding of this paper shows that the Humour elements are correlated to the spontaneous response and behaviour of the audience such as laughing and smiling. Every individual has different spontaneous response and behaviour as it depends on the audienceâ€™s interest, inclination and also understanding towards a humour issue displayed to them. Based on two episodes of the Karoot Komedi, the Dramaturgy in Comedy Sabri Yunus applied the Humour techniques during the performance. To sum up each episode as a whole, each episode are assessed based on 4 categories which are Language, Logic, Identity and action.